Letter from Rosa Bredig to Max Bredig, June 14, 1927 - Bredig, Rosa (1927)
Rosa Bredig (1877-1933) writes to her son, Max Bredig (1902-1977), about his room and board options in Göttingen, where he is working as an assistant scientist.
Keywords: Bredig, Rosa, 1877-1933; Bredig, Max Albert, 1902-1977